A study on the consequence of swift heavy ion irradiation of Zn–silica nanocomposite thin films: electronic sputtering - Pannu, Compesh; Singh, Udai B.; Agarwal, Dinesh. C.; Khan, Saif A.; Ojha, Sunil; Chandra, Ramesh; Amekura, Hiro; Kabiraj, Debdulal; Avasthi, Devesh. K. (Beilstein Journal of Nanotechnology, 2014)
Zn–silica nanocomposite thin films with varying Zn metal content, deposited by atom beam sputtering technique were subjected to 100 MeV Ag ion irradiation. Rutherford backscattering spectrometry reveals the loss of Zn with irradiation, which is observed to be greater from thin films with lower Zn content. The sputtered species collected on carbon-coated transmission electron microscopy (TEM) grids consist of Zn nanoparticles of sizes comparable to those present in the nanocomposite thin film. The process of size-dependent electronic sputtering of Zn is explained on the basis of an inelastic thermal spike model. The possibility of direct cluster emission is explained by pressure spike built inside the track, initiated by a temperature spike.
Keywords: ion irradiation; nanocomposites; pressure spike; Rutherford backscattering spectrometry; transmission electron microscopy